ANALISIS KANDUNGAN TIMBAL PADA LIPSTIK IMPOR DAN DALAM NEGERI SERTA TINGKAT PENGETAHUAN KONSUMEN DAN PEDAGANG TERHADAP LIPSTIK YANG BEREDAR DI PASAR PETISAH KOTA MEDAN TAHUN 2015 - martha helen sihite; evi naria; nurmaini * (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Lipsticks are now becoming the primarily daily needs for women. Some lipsticks has already contaminated by heavy metal for example lead. Lead in lipstick goes in to the body through mouth and absorbed through skin. The knowledge of consumers and sellers is really important to know because it will effect the way of choosing their lipsticks products that they want to use or sell. The purpose of this research is to know how much lead was being used in imported lipsticks and in domestic lipsticks products as well as to know how far the consumers’ and the sellers’ knowledge about lipsticks which sold at Petisah Market in Medan. This research is a descriptive research. The population of consumers are all the consumer who bought lipsticks in the location of research. The sample of consumers is 30 that has been taken by accidental sampling. The population of the sellers is 25. The sample of sellers is 25 that has been taken by total sampling. The data was analyzed by descriptive in table and narration. The result of this research showed that 8 samples of lipstick that have been tested, contained lead with the range between 0,121-2,010 ppm. The level of consumers’ knowledge was divided in to the intermediate level of knowledge about (20%)  and the good level of knowledge about (80%). The level of sellers’ knowledge was divided in to the intermediate level of knowledge about (20%)  and the good level of knowledge about (80%). The conclusion is all the sample of lipsticks products contained lead. The content is still acceptable according to the regulation of BPOM RI that is <20 mg/kg. Both of consumers’ and sellers’ knowledge are in good level of knowledge  which is 80%. Suggested to BPOM RI to give more information about lipsticks that consisting lead to the society.